Microbial amperometric biosensor for online herbicide detection: Photocurrent inhibition of Anabaena variabilis. (10th April 2019) - Tucci, Matteo; Grattieri, Matteo; Schievano, Andrea; Cristiani, Pierangela; Minteer, Shelley D.
Abstract: A microbial biosensor based on the cyanobacteria Anabaena variabilis was developed for online herbicide detection through inhibition of generated photocurrent. Specifically, atrazine and diuron were employed as model photosynthesis-inhibiting herbicides. To fabricate the biosensor, bacterial cells were immobilized on a carbon felt electrode using alginate as an entrapping polymer and p-benzoquinone (BQ) as the redox mediator to sustain the electron transfer. The current generated by the photo-bioelectrocatalytic oxidation of water was evaluated. During the calibration, an immediate concentration-dependent decrease of the photocurrent was observed after the injection of the tested herbicides. The biosensor showed a sensitivity of −24.6 μA μM −1  cm −2 towards atrazine up to 0.56 μM. As diuron is a much stronger photosynthesis inhibitor, the biosensor allows only turn on/turn off detection for this compound. In order to avoid the release of the mediator in solution, the encapsulation of BQ in the polymer was tested. Addition of activated carbon was necessary to create a conductive network inside the alginate matrix, enabling to achieve a sensitivity of −7.7 μA μM −1  cm −2 towards atrazine up to 131 μM (lower limit of detection 64 nM). Therefore, not only the entrapment prevented the release of BQ in solution, but improved the operating range of the sensor, with a limited decrease of sensitivity that does not hinder its application. These characteristics make the biosensor suitable for environmental analysis, opening for the on-line monitoring of herbicides. Graphical abstract: Image 1 Highlights: A microbial amperometric biosensor was developed for online herbicide detection. Alginate entrapment avoided the mediator release during the whole test (6 h). Entrapment of the mediator allowed broader linear range of the biosensor.